Beeldvorming rond adel en ridderschap bij Froissart en de Bourgondische kroniekschrijvers - Buylaert, F.; Dumolyn, J. (BMGN - Low Countries Historical Review, 2008)
The Representation of Nobility and Chivalry in the Literature of Froissart and the Burgundian ChroniclersThis article discusses the representation of nobility and chivalry in the historiographical literature of Jean Froissart and his fifteenth-century followers. By analysing the discourse of those chronicles, this article intends to focus on the social functions of this literary tradition for its intended public; the nobles and state officials of the Burgundian-Habsburg court. As such, this publication questions the existing interpretation of the remarkable emphasis of those chroniclers on virtue as the source of ‘true nobility’ as an attempt by ambitious officials and intellectuals to obtain a noble status. The social significance of those chronicles resides in the fact that they were important for the definition and dissemination of a set of norms that governed the public behaviour of nobles. This article is part of the special issue 'The history of the nobility in the Netherlands and Belgium'.